Penerapan Google Form Untuk Evaluasi Kehadiran Perkuliahan Taruna-Taruni Teknika PDP UHT - Saktiono, Maxima Ari (Universitas Hang Tuah, 2019)
Attendance is an activity of recording the number of attendance at an event that produces attendance data that can be used for various purposes. In each activity attendance must be done to attend attendance information. Likewise, the teaching and learning process on campus is also carried out absenteeism. The purpose of this attendance is to find out the number of attendance of students / cadets to determine whether the student / cadets can take the final semester exams and to add grades. The attendance system that is carried out up to now in the Program Diploma Pelayaran Universitas Hang Tuah still uses manual paper attendance that is integrated with lecture documents. Every lecture will begin cadets takes lecture documents in the Administration Room which are put in one folder. Attendance must be done by cadets who are present and may not be represented. If a cadet is unable to attend following a lecture due to illness, permission is considered to be entered if accompanied by a letter from the doctor or from the student's guardian and is known / initialed by the lecturer in charge during the lecture. After finishing the lecture, the lecture map is returned to the administration room. Person of administrtion room will recapitulate all attendance lectures manually. Taking attendance data that is done manually has many shortcomings, such as cheating cadets in filling attendance, invalid data when data is entered incorrectly, loss or damage of existing data, lack of efficiency and effectiveness in data processing . In this study the authors utilize information system technology to create attendance for cadets in PDP by utilizing one of the features on Google, Google Form. Google Form or the so-called Google Form is a useful tool to help plan events, send surveys, give students or others quizzes or gather information easily in an efficient way. Forms are also linked to spreadsheets, Google forms are part of Google Drive.